2015
DOI: 10.1159/000369702
|View full text |Cite
|
Sign up to set email alerts
|

Hyperketonemia (Acetoacetate) Upregulates NADPH Oxidase 4 and Elevates Oxidative Stress, ICAM-1, and Monocyte Adhesivity in Endothelial Cells

Abstract: Background/Aims: The incidence of developing microvascular dysfunction is significantly higher in type 1 diabetic (T1D) patients. Hyperketonemia (acetoacetate, β-hydroxybutyrate) is frequently found along with hyperglycemia in T1D. Whether hyperketonemia per se contributes to the excess oxidative stress and cellular injury observed in T1D is not known. Methods: HUVEC were treated with ketones in the presence or absence of high glucose for 24 h. NOX4 siRNA was used to specifically knockdown NOX4 expression in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 53 publications
(62 reference statements)
1
72
0
Order By: Relevance
“…Leeson et al have demonstrated that carriage of an endothelial nitric oxide synthase polymorphism was associated with functional changes in the endothelium and in cardiovascular disease [45]. Furthermore, uncoupling the endothelial nitric oxide synthase resulting in superoxide anion (O 2 -) formation instead of nitric oxide (NO) causes diabetic endothelial dysfunction [8,9,46]. It has been reported that NO preservation protected endothelial dysfunction under high glucose conditions [47].…”
Section: Discussionmentioning
confidence: 99%
“…Leeson et al have demonstrated that carriage of an endothelial nitric oxide synthase polymorphism was associated with functional changes in the endothelium and in cardiovascular disease [45]. Furthermore, uncoupling the endothelial nitric oxide synthase resulting in superoxide anion (O 2 -) formation instead of nitric oxide (NO) causes diabetic endothelial dysfunction [8,9,46]. It has been reported that NO preservation protected endothelial dysfunction under high glucose conditions [47].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Kanikarla-Marie and Jain, 2015;Liu et al, 2015;Seebacher et al, 2015;Wang et al, 2015) have reported that high glucose concentrations lead to over-aggregation of ROS in the body, which results in oxidative stress injury and affects the cell growth and survival cycle. This causes abnormal metabolism and dysfunction in cells, as well as apoptosis, ultimately resulting in diabetic vascular complications, ischemic necrosis, ischemic neuropathy, and paresthesia in the affected limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NOX4 appears to be protective in the aorta as deletion or inhibition of NOX4 resulted in increased atherosclerosis associated with increased inflammation in both vascular and immune cells 37. Activation of PKC and the generation of AGEs, both of which are upregulated in the diabetic environment, have been shown to activate NOX isoforms in monocytes and macrophages, and drive an increase in the expression of pro‐inflammatory genes such as IL‐6, monocyte chemoattractant protein 1(MCP‐1), and intercellular adhesion molecule 1 (ICAM‐1) 38, 39. By activation of these pathways, it has been demonstrated that inflammation is increased throughout the body, leading to the generation of ROS.…”
Section: Diabetes and Cardiovascular Diseasementioning
confidence: 99%